Review article: mesenchymal stromal cell therapy for inflammatory bowel diseases. Issue 2 (22nd November 2016) - Grégoire, C.; Lechanteur, C.; Briquet, A.; Baudoux, É.; Baron, F.; Louis, E.; Beguin, Y.
Summary: Background: Inflammatory bowel diseases (IBD) are chronic relapsing diseases in which pro‐inflammatory immune cells and cytokines induce intestinal tissue damage and disability. Mesenchymal stromal cells (MSCs) exert powerful immunomodulatory effects and stimulate tissue repair. Aim: To review the current data on mesenchymal stromal cell therapy in IBD. Method: We searched PubMed and 'ClinicalTrials.gov' databases using the terms 'mesenchymal stromal cells', 'mesenchymal stem cell transplantation', 'inflammatory bowel diseases', 'Crohn disease' and 'colitis, ulcerative'. Additional publications were identified from individual article reference lists. Results: MSCs include inhibition of Th1/Th17 lymphocytes and recruitment of regulatory T lymphocytes, induction of antigen‐presenting cells into a regulatory‐like profile, and stimulation of epithelial cell differentiation and proliferation. More than 200 patients with refractory fistulas have been treated with local injections of MSCs, resulting in complete response in more than half, and in overall response in approximately two thirds of patients. In refractory luminal Crohn's disease, 49 cases of systemic MSC infusions have been reported, while trials with autologous MSCs resulted in mitigated responses, studies using allogeneic MSCs were promising, with around 60% of patients experiencing a response and around 40% achieving clinical remission. Conclusions: Mesenchymal stromal cells might represent a promising therapy for IBD, especially for Crohn's disease. There remain many unsolved questions concerning the optimal origin and source of mesenchymal stromal cells, dosage and modalities of administration. Moreover, mesenchymal stromal cells still need to prove their effectiveness compared with conventional treatments in randomised controlled trials.